Existence of Triple Positive Solutions for Second-Order Discrete Boundary Value Problems. (4th January 2007) - Guo, Yanping; Zhang, Jiehua; Ji, Yude
Abstract : By using a new fixed-point theorem introduced by Avery and Peterson (2001), we obtain sufficient conditions for the existence of at least three positive solutions for the equationΔ 2 x ( k − 1 ) + q ( k ) f ( k, x ( k ), Δ x ( k ) ) = 0, fork ∈ 1, 2, …, n − 1 , subject to the following two boundary conditions:x ( 0 ) = x ( n ) = 0 orx ( 0 ) = Δ x ( n − 1 ) = 0, wheren ≥ 3 .